Yoga Meningkatkan Kualitas Hidup Wanita Menopause: Scoping Review Berbasis MENQOL - M. Kus Fitriani Fruitasari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Background: Menopause have a significant impact on a woman's quality of life. Yoga has been proposed as a non-pharmacological intervention to improve the quality of life of postmenopausal women. This scoping review aims to identify and analyze existing literature regarding the effectiveness of yoga interventions on the quality of life of menopausal women as measured by the Menopause-Specific Quality of Life Questionnaire (MENQoL). Methods: A literature search was conducted on electronic databases including PubMed, Scopus, and Web of Science for studies published up to 2024. Inclusion criteria included yoga intervention studies in menopausal women with measurements using MENQoL. Data were extracted regarding study characteristics, type of yoga intervention, duration, frequency, and MENQoL outcomes. Results: Of a total of 245 articles identified, 18 studies met the inclusion criteria. The majority of studies reported significant improvements in total MENQoL scores and subdomains after yoga intervention. The most commonly used type of yoga is Hatha yoga which is adapted for menopause. The duration of the intervention varied from 4 to 16 weeks, with a frequency of 2–3 sessions per week. Conclusion: This scoping review shows that yoga can improve the quality of life of menopausal women as measured by MENQoL. Further research with more rigorous designs is needed to determine the optimal yoga protocol and its long-term effects.